PARATUMAROCERAS, A NEW PARAGASTRIOCERATID GENUS (AMMONOIDEA) FROM THE LOWER PERMIAN OF THE WESTERN VERKHOYANSK REGION - Kutygin R.V. (My University, 2003)
Based on the ontogeny of the genus Tumaroceras, a new genus Paratumaroceras, with the type species P. ruzhencevi sp. nov., is proposed. New taxa are described.
Keywords: Ammonoidea; Paragastrioceratidae; new taxa; Lower Permian; northeastern Russia; Paleozoic::Permian; Палеозой::Пермская